Protective and decorative coatings : special studies - Mattiello, Joseph J. (Wiley)
Contiene: The theoretical and practical aspects of wetting; Theory of grinding; Color; Hiding; The adhesion of dried coatings; Adsorption, permeability, water resistance, and structure of organic surface coating; Livering of printing inks; Microscopy in the paint and varnish industry; High-vacuum technology; Emulsions; Ultraviolet absorption studies of drying oils.